Study of Modulation of Host-cell Death by Vibrio cholerae Porin OmpU and the Underlying Mechanism - Gupta, Shelly (IISERM, 2016)
There is no abstract
Keywords: Biology; Vibrio Cholerae; Porins; Diarrheal Disease; Gram negative Bacteria